Предмет: Алгебра,
автор: Анoнuм
За ответ дам 25 баллов
Помогите решить уравнение 2х(1-х)-3(х+2)=х(1+2х)
Заранее спасибо))
Ответы
Автор ответа:
0
-2x²+2x-3x-6=x+2x²
-2x²+2x-3x-6-x-2x²
-4x²-2x-6=0
D=(-2)²-4*(-24)=4+96=100
√D=10
X¹=-10-2/8=-12/8=1 1/2
X²=-2+10/8=8/8=1
-2x²+2x-3x-6-x-2x²
-4x²-2x-6=0
D=(-2)²-4*(-24)=4+96=100
√D=10
X¹=-10-2/8=-12/8=1 1/2
X²=-2+10/8=8/8=1
Похожие вопросы
Предмет: Қазақ тiлi,
автор: almaevao33
Предмет: Математика,
автор: Оля154355
Предмет: Английский язык,
автор: symyrbaevaanargul
Предмет: Экономика,
автор: Аnnuchka
Предмет: Алгебра,
автор: danila0412